Knowledge, attitude and practice of people with HIV regarding a healthy lifestyle: clinical trial - Maria Amanda Correia Lima; Gilmara Holanda da Cunha; Marcos Venícios de Oliveira Lopes; Marina Soares Monteiro Fontenele; Larissa Rodrigues Siqueira; Ane Kelly Lima Ramalho (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To evaluate the effectiveness of an educational booklet on the knowledge, attitude and practice of a healthy lifestyle in people with HIV. Methods: Randomized clinical trial with 75 intervention group patients using the booklet, and 75 control group patients undergoing usual service care. Data collection occurred in four moments, with a Survey pertaining Knowledge, Attitude and Practice. Nonparametric analysis of variance of repeated measures was used. Results: 70 participants in the intervention group and 74 in the control group completed the study. In terms of knowledge, there was no difference between groups, the booklet impact came late, increasing after reassessments. In attitudes, there was a difference between groups in the two- and four-month reassessments compared to the baseline. In practices, there was a difference in the intervention group compared to the control group at two, four, and six months compared to baseline. Conclusion: The booklet was effective in improving healthy lifestyle knowledge, attitudes, and practices in people with HIV.